Maternal folic acid supplement use/dietary folate intake from preconception to early pregnancy and neurodevelopment in 2-year-old offspring: the Japan Environment and Children's Study. Issue 12 (28th December 2022) - Suzuki, Taeko; Nishigori, Toshie; Obara, Taku; Masumoto, Toshio; Mori, Miyuki; Murata, Tsuyoshi; Kyozuka, Hyo; Ogata, Yuka; Sato, Akiko; Sampei, Mari; Takahashi, Toshifumi; Shinoki, Kosei; et al.
Abstract: We evaluated the association between maternal prenatal folic acid supplementation/dietary folate intake and motor and cognitive development in 2-year-old offspring using data from the Japan Environment and Children's Study database. Neurodevelopment of 2-year-old offspring were evaluated using the Kyoto Scale of Psychological Development 2001. In total, data of 3839 offspring were analysed. For folic acid supplementation, a multiple regression analysis showed that offspring of mothers who started using folic acid supplements before conception had a significantly lower developmental quotient (DQ) in the postural-motor DQ area than offspring of mothers who did not use them at any time throughout their pregnancy (partial regression coefficient (B) −2·596, 95 % CI −4·738, −0·455). Regarding daily dietary folate intake from preconception to early pregnancy, a multiple regression analysis showed that the group with ≥ 200 µg had a significantly higher DQ in the language-social area than the group with <200 µg. The DQ was higher in the ≥ 400 µg group (B 2·532, 95 % CI 0·201, 4·863) than the 200 to <400 µg group (B 1·437, 95 % CI 0·215, 2·660). In conclusion, our study showed that maternal adequate dietary folate intake from preconception to early pregnancy has a beneficial association with verbal cognition development in 2-year-old offspring. On the other hand, mothers who started using folic acid supplements before conception had an inverse association with motor development in 2-year-old offspring. There were no details on the amount of folic acid in the supplements used and frequency of use. Therefore, further studies are required.